Conducting and Publishing Research in Developing Countries: Challenges and Solutions. Issue 1 (13th October 2021) - Potnis, Devendra; Gala, Bhakti; Lwoga, Edda Tandi; Islam, Anwarul; Warraich, Nosheen; Keah, Humphrey; Rorissa, Abebe
Abstract: Most of the knowledge in the library and information science (LIS) discipline is created and published by researchers in developed countries. Two roundtable sessions of ASIS&T SIG‐III with the ASIS&T Africa Chapter and ASIS&T South Asia Chapter, in early 2021, confirmed "the lack of a conducive research environment" as the primary reason for this inequality in the discipline and called for systematic efforts, like this panel, to (a) create awareness about this inequality and (b) start building a global support system for LIS researchers in developing countries. In the first 30 minutes of this panel, six LIS scholars with cultural roots, academic training, and research experience in developing countries will illustrate common challenges to conducting and publishing research in developing countries. In the next 30 minutes, attendees will be divided into groups, with each group facilitated by a panelist, to brainstorm solutions for addressing the challenges related to academic training for conducting and publishing research, accessing resources, institutional support, opportunities for research collaboration and funding, fieldwork, analyzing data, composing manuscripts, and finding mentors, among others. In the last 30 minutes, each group will present its findings.